The Effect of Gallic Acid on Pituitary-Ovary Axis and Oxidative Stress in Rat Model of Polycystic Ovary Syndrome - Bibi Fatemeh Mazloom; Mohammad Amin Edalatmanesh; Ebrahim Hosseini (Report of Health Care, 2017)
Introduction: The polycystic ovary syndrome (PCOS) carried along with hormonal– metabolic disorders, oxidative stress and ovulation dysregulation. Several studies have shown the role of Gallic acid (GA) as a potent antioxidant in oxidative stress induced disorders. Considering the antioxidant properties of GA, we investigate the effect of GA on the serum level of pituitary-ovary axis hormones and activity of ovary tissue antioxidant enzymes of PCOS model was studied. Methods: 32 Wistar female rats were divided into four groups: Control, PCOS+Saline, PCOS+GA50, PCOS+GA100. PCOS was induced by single muscular injection of Estradiol valerate (4 mg/kg/BW).Then, GA was prescribed with doses of 50 and 100 mg/kg for 21 days, orally. At the end of treatment period, serum levels of LH, FSH, Estradiol, testosterone and progesterone as well as the tissue level of dismutase superoxide enzymes (SOD), catalase (CAT) and Malondialdehyde (MDA) in the ovaries were measured by ELISA technique. Differences between data were analyzed by one way ANOVA and the p ˂ 0.05 was considered statistically significant. Results: Levels of LH, Estradiol and testosterone as well the MDA in treatment group with GA were increased significantly compared to the PCOS group (p ˂ 0.05), while the serum level of FSH and progesterone and tissue level of SOD and CAT enzymes were increased significantly in GA-treated groups than the PCOS group (p ˂ 0.05). Conclusion: GA modifies the level of sex hormones in PCOS model by increase of antioxidant enzymes activity.